TerraSAR-X Capabilities in Polar Regions - Floricioiu, Dana; Gottwald, Manfred; Diedrich, Erhard; Roth, Achim; Eineder, Michael (2008)
DLR participates in a coordinated plan established by the space agencies for the optimum use of SAR acquisitions over the Artic and Antarctica for the remaining period of IPY and beyond. Due to the specific advantages of the X-band in respect to snow and ice properties and the high spatial resolution of the data, the contribution of TerraSAR-X focuses on topics like mapping of seasonal snow cover at high latitudes, ice sheet velocity, velocity fields of slow and fast moving glaciers, permafrost, generation of DEMs, sea ice classification. These are reflected in a coordinated proposal which is prepared by DLR and the scientific community as part of the common polar SAR acquisition plan.